Development of an online counseling framework for overseas Filipino workers - Peralta, Marlon M.; Cauyan, Jaclyn Marie Lomibao; Pedrajita, Jose Q.; Que, Elenita N. (Quezon City College of Education, University of the Philippines Diliman, 2018)
This study aimed to create a Philippine culture-based online counseling framework for the Overseas Filipino Workers (OFWs) and explore the use of said framework. It was both qualitative and quantitative in nature, involving a two-stage process. During the first stage, there were 33 OFWs who participated in the online interview. The findings highlighted the perceptions of OFWs about counseling and online counseling, their concerns, and coping mechanisms. Using Grounded Theory approach, the answers were gathered, organized, and analyzed which led to the formation of an emergent framework. During the second stage, the emergent framework was pilot tested to 10 OFWs who underwent 8-10 sessions of online counseling. It also underscored the vital role of Filipino psychology and Philippine-culture based techniques in the counseling process. The results showed that online counseling can be used as a direct intervention to address the counseling needs of the OFWs. The study contributes significantly to theory by considering Filipino psychology and the disposition of OFWs in conducting counseling using the online platform. Specifically, this study offers insights on how the utilization of Philippine-culture based techniques in the counseling process can result in gaining more information from the client which serve as the basis of the counselor in providing the appropriate assistance needed, thus, resulting in the empowerment of the OFWs. The study has implications on the need for counseling practitioners to spread awareness about online counseling and its effectiveness, for educational institutions to review their counseling services and programs to explore the use of online counseling, and for government and non-government institutions that cater to OFWs to ensure that the latter have access to online counseling.
Thesis
Includes bibliographical references (213-224 leaves).
Keywords: Foreign workers, Filipino -- Counseling of; Filipinos -- Employment -- Foreign countries